Media, Margins and Popular Culture
XIII, 264 p.
Keywords: This collection brings together leading research on contemporary and popular culture, focussing on marginalised voices and representations; socially marginalised, marginalised in media and media scholarship. It spans five continents, with contributions on topics like gender, sexuality, nation, disability, disciplinary boundaries, youth and age.